Ostracods as proxies for marginal marine to non-marine intervals in the mid-Cretaceous carbonate platform of the Central Tunisian Atlas (North Africa): Response to major short-term sea-level falls. (January 2021) - Trabelsi, Khaled; Sames, Benjamin; Nasri, Ahmed; Piovesan, Enelise Katia; Elferhi, Faycel; Skanji, Ahmed; Houla, Yassine; Soussi, Mohamed; Wagreich, Michael
Abstract: Two non-marine to marginal-marine intervals have been identified by ostracod assemblages in the mid-Cretaceous carbonate platform of the Central Tunisian Atlas, the deposits of which belong to the Orbata Formation. The first non-marine interval has been recorded within member Unit 2b of the Orbata Formation which yielded the first lower Aptian ostracod fauna composed of Alicenula ? leguminella, Vecticypris polita, Cypridea ventriosa, Perissocytheridea altesulcata sp. nov., Harbinia ? cf. sinuata, Hourcqia aff. bateke, Ovocytheridea nuda, Bythocypris ? pythagorasi sp. nov., Paracypris lusitanicus and Paracypris chekhmai sp. nov. The assemblages indicate continental to marginal-coastal environment and lower Aptian emergence of the Orbata Platform, and are interpreted as response to an earliest Aptian 3rd-order (0.5–3 myr) sea-level fall event of major amplitude. A second lowermost Albian ostracod fauna, recorded within members Unit 5b, 6 of the Orbata Formation, is composed of Candonopsis carthaginensis sp. nov., Cypridea quadrangulata, Virgatocypris kechoulaensis, Alicenula ? leguminella, Vecticypris polita, Stenestroemia mosensis, Perissocytheridea kouminiensis sp. nov., Hourcqia aff. bateke, Dolocytheridea bosquetiana, Dolocytheridea donzei sp. nov., Ovocytheridea anterocompressa, Paracypris dubertreti, Paracypris mdaouerensis, Clithrocytheridea espichelensis, Bythocypris ? multagracilis sp. nov. and Bythocypris dorsogibba sp. nov. The assemblages indicate another interval of non-marine to marginal-marine depositional settings as direct response to a prominent eustatic latest Aptian to earliest Albian sea-level fall event that enhanced the quasi-total emersion of the Central Tunisian Atlas palaeogeographic domain. Hence, the two studied faunas herein allow us to define two stratigraphic key surfaces of regional utility giving new insights into the chronostratigrahic subdivision of the Orbata carbonate platform, especially in supporting a previously neglected early Albian age of its upper part (Unit 5b, 6 and 7) and allow the regional stratigraphic correlation of these key surfaces in the Central Tunisian Atlas (CTA) domain. Accordingly, our results not only disprove the previous consideration of an uppermost Aptian–lower Albian hiatus but also implicate the necessity to redefine and review the previous palaeogeographic and tectono-sedimentary schemes of the CTA as suggested for almost fourty years. Graphical abstract: Image 1 Highlights: Ostracod assemblages from two mid-Cretaceous 'regional discontinuities' of Central Tunisian Atlas described. 6 new mid-Cretaceous ostracod species first time described from Gondwana. Major eustatic sea-level fall events KAp1 and KAp7 well calibrated by ostracods, charophytes, Strontium isotope and dinosaurs. New chronostratigraphic scheme of the Central Tunisian Carbonate platform established.